Author correction: identification of multiple risk loci and regulatory mechanisms influencing susceptibility to multiple myeloma - Went, Molly; Bertsch, Uta; Bandapalli, Obul Reddy; Brenner, Hermann; Canzian, Federico; Chen, Bowang; Försti, Asta; Goldschmidt, Hartmut; Hemminki, Kari; Hillengaß, Jens; Thomsen, Hauke; Weinhold, Niels (Nature Communications, 2019)
The original version of this Article contained an error in the spelling of a member of the PRACTICAL Consortium, Manuela Gago-Dominguez, which was incorrectly given as Manuela Gago Dominguez. This has now been corrected in both the PDF and HTML versions of the Article. Furthermore, in the original HTML version of this Article, the order of authors within the author list was incorrect. The PRACTICAL consortium was incorrectly listed after Richard S. Houlston and should have been listed after Nora Pashayan. This error has been corrected in the HTML version of the Article; the PDF version was correct at the time of publication.
Gesehen am 16.07.2019
Molly Went, Asta Försti, Niels Weinhold, Uta Bertsch, Obul R Bandapalli, Bowang Chen, Jens Hillengass, Federico Canzian, the PRACTICAL consortium Hauke Thomsen, Hartmut Goldschmidt, Kari Hemminki [und weitere]; the PRACTICAL consortium Hermann Brenner [und weitere]